2002
DOI: 10.1590/s1516-35982002000100015
|View full text |Cite
|
Sign up to set email alerts
|

Desempenho de Novilhos Red Angus Superprecoces, Confinados e Abatidos com Diferentes Pesos

Abstract: Foi avaliado o desempenho em confinamento de machos Red Angus confinados a partir dos oito meses de idade, quando apresentavam peso vivo médio de 189 kg, até atingirem os seguintes pesos pré-determinados (PA): 340, 370, 400 e 430 kg. O número de dias necessários para atingir os respectivos pesos foram de 114, 144, 168 e 209 dias, com 12, 13, 14 e 15 meses de idade. Os animais foram alimentados com uma dieta contendo 13,13% de proteína bruta e relação volumoso (silagem de milho):concentrado de 56:44. O ganho de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
0
31

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(46 citation statements)
references
References 12 publications
3
12
0
31
Order By: Relevance
“…The data found in the literature about DMI according to slaughter weight are contradictory. Bailey et al (1985), Galvão et al (1991), Jorge et al (1997) and Mello (2007) observed increases in DMI, expressed in kg/day, of diets as the slaughter weight increased, whereas Van Koevering et al (1995), Costa et al (2002a), Arboitte et al (2004a) and Cruz et al (2004a) did not observe any alteration. This demonstrates that there is variation in ingestion and that other factors, such as genetics, weight at maturity and type of diet, can interfere with this parameter.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…The data found in the literature about DMI according to slaughter weight are contradictory. Bailey et al (1985), Galvão et al (1991), Jorge et al (1997) and Mello (2007) observed increases in DMI, expressed in kg/day, of diets as the slaughter weight increased, whereas Van Koevering et al (1995), Costa et al (2002a), Arboitte et al (2004a) and Cruz et al (2004a) did not observe any alteration. This demonstrates that there is variation in ingestion and that other factors, such as genetics, weight at maturity and type of diet, can interfere with this parameter.…”
Section: Resultsmentioning
confidence: 95%
“…Thus, determining the ideal slaughter weight for animals that meets the requirements of the commercialization and distribution systems is essential, once slaughterhouses prefer heavier animals and those with adequate fat degree, which is not interesting to the farmer, who needs more time for animals to stay in confinement, which may have a direct effect on productive and economic efficiency (Costa et al, 2002a;Restle et al, 2007). When slaughterhouses adopt bonus programs, the uniformity of the animals; sex; age; fat cover; and weight at slaughter are criteria utilized for a differentiated remuneration.…”
Section: Introductionmentioning
confidence: 99%
“…O estudo de carcaças permite avaliar a qualidade do produto final de um sistema de produção (Costa et al, 2002). E segundo Delgado (2000b), a qualidade da carcaça relaciona-se indiretamente com aspectos de qualidade da carne bovina.…”
Section: Qualidade Da Carcaça Bovinaunclassified
“…A variação de peso da carcaça é de relevância econômica aos frigoríficos, ao considerar que materiais de pesos diferentes na linha de abate requerem a mesma mão-de-obra e tempo de processamento na desossa (Costa et al, 2002).…”
Section: Qualidade Da Carcaça Bovinaunclassified
See 1 more Smart Citation